Validity of Adult Psychopathology Model Using Psychiatric Patient Sample from a Developing Country: Confirmatory Factor Analysis - Naser Abdulhafeeth Alareqe; Siti Aishah Hassan; Engku Mardiah Engku Kamarudin; Musheer A. Aljaberi; Mohamad Sahari Nordin; Nadeem Mohamed Ashureay; Lubna Ali Mohammed (Mental Illness)
Objectives. This study is aimed at testing and validating the two-factor measurement model of the Millon Clinical Multiaxial Inventory (MCMI). Specifically, this paper reported construct validity, particularly focusing on convergent and discriminant validities of the internalizing-externalizing MCMI model of adult psychopathology using a psychiatric sample from a developing country, the Republic of Yemen. Methods. MCMI was distributed among 232 outpatients from the Hospital of Taiz City and two private psychiatry clinics in Yemen; data were collected using structured interviews over four months. We used exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to explore and confirm the latent structure MCMI and verify the evidence of convergent and discriminant validity. Results. The CFA results indicated that MCMI was a good fit for the internalizing-externalizing two-factor model of adult psychopathology, comparative fit index CFI=0.95, and RMSEA=0.07. The results of the CFA provide evidence of convergent and discriminant validity characterized by MCMI with the internalizing-externalizing model. Conclusion. The adult psychopathology of internalizing-externalizing is a valid measurement model of MCMI with ten personality disorders and eight clinical syndromes.